Intraarticular osteochondroma of distal humerus, proximal radius and ulna - Chaudhary, P; Shrestha, B P; Khanal, G P; Maharjan, R; Rijal, R; Paneru, S R; Karn, N K; Rauniyar, R K; Sinha, A K (Health Renaissance, 2015)
Intraarticular location of osteochondroma is very rare and only few such cases have been reported in the literature previously. Intraarticular osteochondroma generally appears as a single loose body or multiple loose bodies in the joint cavity. We present here a case of 38-year-old lady who presented in the out patients department of Orthopaedics, BPKIHS, Dharan with pain and swelling in and around the right elbow joint for previous one year. She sought treatment in many centers of easternNepalandB.PKoiralaCancerHospital, Bharatpur in the line of soft tissue tumor. Due to its rarity and unique characteristics, we herein report the case of intraarticular osteochondroma of elbow joint. Health Renaissance 2014;12(2): pp: 137-139